2021
DOI: 10.3390/ijms22041941
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia: Cardiotonic Steroids, Fibrosis, Fli1 and Hint to Carcinogenesis

Abstract: Despite prophylaxis and attempts to select a therapy, the frequency of preeclampsia does not decrease and it still takes the leading position in the structure of maternal mortality and morbidity worldwide. In this review, we present a new theory of the etiology and pathogenesis of preeclampsia that is based on the interaction of Na/K-ATPase and its endogenous ligands including marinobufagenin. The signaling pathway of marinobufagenin involves an inhibition of transcriptional factor Fli1, a negative regulator o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…As normal pregnancy is associated with fluid and sodium retention [ 51 ], the attention around the possible role of EDLF in pregnancy arose after their discovery [ 52 ]. In 1984, two research teams found an endogenous factor that cross-reacted with digoxin antibodies in the serum of pregnant women, and increased levels of this factor were associated with hypertensive disorders of pregnancy [ 53 , 54 ].…”
Section: Endogenous Digitalis-like Factors (Edlf)mentioning
confidence: 99%
“…As normal pregnancy is associated with fluid and sodium retention [ 51 ], the attention around the possible role of EDLF in pregnancy arose after their discovery [ 52 ]. In 1984, two research teams found an endogenous factor that cross-reacted with digoxin antibodies in the serum of pregnant women, and increased levels of this factor were associated with hypertensive disorders of pregnancy [ 53 , 54 ].…”
Section: Endogenous Digitalis-like Factors (Edlf)mentioning
confidence: 99%
“…Na/K-ATPase (Na + pump) inhibitors, including digitalis-like cardiotonic steroid marinobufagenin (MBG), have been recognized as one of the classic agents seen in elevating blood pressure in response to sodium loads [53]. The potent endogen steroid MBG, also produced by the placenta, is included in the pathogenesis in reference to PE [54].…”
Section: Hypervolemic Maternal or Term Pementioning
confidence: 99%
“…As a result, in PE, due to elevated MBG, umbilical arteries lose their capacity to relax although their contractile response remains unchanged [ 5 ]. Therefore, in PE patients, heightened MBG plasma levels represent a potential target for therapy and for the immunoneutralization of MBG [ 14 ]. We developed an anti-MBG monoclonal antibody that possesses a remarkable capacity to reduce blood pressure and cardiac fibrosis in rats with renal failure [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%